An Overview of Antibiotic Solubility Based on Reconstitution Time - Roosmeilany, R. Meitha; Sumardi, Uun; Supiani, Epa; Syabariyah, Sitti; Rahmawati, Endah Yuliany (The Indonesian Institute of Science and Technology Research, 2025)
The reconstitution of parenteral antibiotics is the process of mixing antibiotic drugs with sterile solutions for intravenous use. According to Indonesian Nursing Law No. 38 of 2014, Article 33, nurses are authorized to provide limited pharmaceutical services, including assisting in drug reconstitution. Errors in the mixing process can lead to incorrect drug dosages or reduced efficacy. This study aims to describe the solubility of antibiotics based on the reconstitution time of antibiotics in the Medical Intermediate Care (MIC) unit at Dr. Hasan Sadikin General Hospital in Bandung. The research method used is quantitative descriptive correlational, utilizing frequency distribution to assess respondent characteristics, the antibiotics used, and their solubility. Central tendency measures are used to determine the mean solubility of antibiotics based on reconstitution time. A total of 66 samples were collected using accidental sampling techniques. The reconstitution procedure used aquabidest (distilled water) and NaCl. The duration of the reconstitution process affected the solubility of the antibiotics. It was concluded that the reconstitution and mixing procedures for parenteral preparations in the MIC unit did not fully meet Good Preparation standards. Antibiotics such as Cefepime, Vancomycin, Cefotaxime, and Meropenem had relatively longer reconstitution times compared to other antibiotics. Nurses should have the knowledge and skills to perform drug reconstitution according to standards. Hospitals should establish drug reconstitution standards to ensure the quality of medications administered to patients, thus preventing an increase in antibiotic resistance.